2020
DOI: 10.1021/acsnano.9b09618
|View full text |Cite
|
Sign up to set email alerts
|

Osteotropic Radiolabeled Nanophotosensitizer for Imaging and Treating Multiple Myeloma

Abstract: Rapid liver and spleen opsonization of systemically administered nanoparticles (NPs) for in vivo applications remains the Achilles’ heel of nanomedicine, allowing only a small fraction of the materials to reach the intended target tissue. Although focusing on diseases that reside in the natural disposal organs for nanoparticles is a viable option, it limits the plurality of lesions that could benefit from nanomedical interventions. Here we designed a theranostic nanoplatform consisting of reactive oxygen (ROS)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 70 publications
1
13
0
Order By: Relevance
“…Distribution of nanostructures to bone marrow is barely studied so far; however, it has been proven that some nanocarriers can be accumulated in bones [ 54 , 55 , 56 ]. Recent studies by Tang et al showed that TiO 2 nanoparticles can be used as an effective, targeted platform for multiple myeloma imaging and treatment [ 57 ]. However, it has also been demonstrated that the biokinetics of nanoparticles significantly differ between widely studied rodent models and primates [ 58 ], considering bone marrow distributions.…”
Section: Discussionmentioning
confidence: 99%
“…Distribution of nanostructures to bone marrow is barely studied so far; however, it has been proven that some nanocarriers can be accumulated in bones [ 54 , 55 , 56 ]. Recent studies by Tang et al showed that TiO 2 nanoparticles can be used as an effective, targeted platform for multiple myeloma imaging and treatment [ 57 ]. However, it has also been demonstrated that the biokinetics of nanoparticles significantly differ between widely studied rodent models and primates [ 58 ], considering bone marrow distributions.…”
Section: Discussionmentioning
confidence: 99%
“…734,735 Most of reported examples of CRIT applications are based on the combination of TiO 2 nanoparticles as photosensitiser material with 68 Ga, 64 Cu, 18 F or 89 Zr radionuclides to generate the CL. [736][737][738][739] Apart of TiO 2 nanoparticles, other materials such as iron oxide NPs and porphyrins have shown a remarkable PDT response in combination with 89 Zr, 740,741 opening a very encouraging field within personalised nanomedicine due to the unique properties of the radiolabelled nanomaterials.…”
Section: Radionuclide Therapymentioning
confidence: 99%
“…Titanium dioxide (TiO 2 ) nanoparticles coated with Tf and radiolabeled with 89 Zr were able to target the BM and image the distribution of nanoparticles in mouse models. Besides, in the presence of 89 Zr, the TiO 2 nanoparticles were able to generate ROS and induce cell death through the apoptosis pathway 209 …”
Section: Nanomedicine‐based Strategies For Multiple Myelomamentioning
confidence: 99%